¿A dónde van los que quieren salir adelante? Estudiantes de nuevas universidades privadas y la búsqueda del éxito: el caso de la Universidad César Vallejo - Seclén Neyra, Eloy (2014)
This paper presents the phenomenon of the private universities that have emerged in our country during the nineties. This increase of alternatives to access to higher education has generated a sense of significant progress in terms of social mobility opportunities for middle class youth. However, we point that this quantitative increase has caused rather a very strong professional market segmentation. That is, it has not reduced educational gaps